Mysteries of Mithra / translated by Thomas J. McCormack - "Cumont, Franz" (New York, 1956)
his brief outline of the comparatively meagre information we possess on what at one time was the most widely spread mystery-institution in the Roman empire, is introductory to the following small volume which will deal with the only Mithriac Ritual known to us. In dealing with this exceedingly instructive Ritual I found that the limits of one booklet would not suffice for an adequate introduction; and without this, I fear, many readers will not be in a position to appreciate the Ritual at its just value.
Keywords: Religion